Factors influencing Uber adoption in Bangladesh and Pakistan - Ummeh Habiba Faria Benteh Rahman; Muhammad Khubaib Zafar (Open Economics, 2020)
The paper's intention is to investigate the behavioral intentions of consumers towards the adoption of Uber with focus on effects of digitalization and shared economy on the adoption of Uber. The aim of the article is to examine the cultural factors of Bangladesh and Pakistan, which are leading people towards adopotion of non traditional source of transport. Particularly, these countries' comparison was not done before by other researchers. Theory of Planned Behavior integrated with Hofstede's Cultural Dimensions has been used to examine the Behavioral Intention of customers of these two countries towards adoption of Uber in the research. A great comparison was done in the study by using factors of TAM, TPB and Hofstede Cultural Models. Dependent variables played important roles in showing positive and negative attitudes on independent variables. This article's findings show that 'Risk' negatively affects the Behavioral Intention. Research data is collected through online close-ended questionnaires from 145 total respondents, which limits the generalization of the study. At the end, where it identified 'female' as a bigger market and provided an opportunity for Uber to categorize the risks prevalent in the society and define new strategies by adapting to the local culture by being a global company. Factors examination produced a great findings which created recommendations for future researchers followed by a conclusion
Keywords: 330; Theory of Planned Behavior; Technology Adoption Model; Hofstede's Cultural Dimensions; Digital Transformation; Shared Economy; Customer's Acceptance